Escherichia coli and Enterococcus faecalis are able to incorporate and enhance a pre-formed Gardnerella vaginalis biofilm. Issue 3 (17th January 2016) - Castro, Joana; Machado, Daniela; Cerca, Nuno
Abstract : Gardnerella vaginalis is the most frequent microorganism found in bacterial vaginosis (BV), while Escherichia coli and Enterococcus faecalis are amongst the most frequent pathogens found in urinary tract infections (UTIs). This study aimed to evaluate possible interactions between UTIs pathogens and G. vaginalis using an in vitro dual-species biofilm model. Our results showed that dual-species biofilms reached significantly higher bacterial concentration than monospecies biofilms. Moreover, visualization of dual-populations species in the biofilms, using the epifluorescence microscopy, revealed that all of the urogenital pathogens coexisted with G. vaginalis . In conclusion, our work demonstrates that uropathogens can incorporate into mature BV biofilms. Abstract : Escherichia coli and Enterococcus faecalis have the ability to incorporate a dual-species biofilms mediated by Gardnerella vaginalis, a key feature important for bacterial vaginosis and possible in urinary tract infections.